An unfinished story - Walker, Boo (Lake Union Publishing, 2020)
Three years after Claire Kite lost her husband David, an aspiring novelist, she finally finds the courage to move on. While going throug David's things, she finds his last, unfinished, manuscript. Whitake Grant is famous for his one and only best-selling novel and is now suffering through a deep midlife crisis. When Claire reaches out to him to finish her husband's novel, he undertakes to understand the man who wrote it and the women he left behind.